Da fé à promoção social: a atividade missionária do Padre Ibiapina - Oliveira, Alberto Rodrigues de (2007)
In the second half of the nineteenth century, society and the catholic church in Brazil experienced a period of great changes. In that period, Father Ibiapina, as a missionary, implemented and developed numerous social works. He characterized his work with a certain charism and in a short period of time, working in groups, constructed a significant number projects in the interior of five northeastern provinces. Through community participation, Ibiapina distributed responsibilities and generated enthusiasm that would lead to welfare services in the communities. He did this with the idea that each community, together with the church, could assume their responsibilities of their own social problems and solve them accordingly to their own possibilities. Sensitive to the regional problems of the brazilian northeast, he made Houses of Charity the base of his activities, especially promoting woman, qualifying them through educational, religious and professional training. Following his missionary project, Ibiapina defined his understanding, by employing religion and its possibilities, bringing social and economical benefits to the rural population, his principle object. Related to a living faith in God, translated in activities, his social works assembled populations that were before scattered and made concrete something more than merely material constructions. All of this established his missionary life as a symbol of achievements and benefits, expressing that an ideal can bring forth to a precarious social reality, existing in a certain time and in a certain society.